Island Capitalization and Coastal Community Resistance in Fighting for Environmental Sustainability Against Corporate Domination in Pari Island Jakarta - Yunsen Ecclesia; Yeby Ma'asan Mayrudin (Social and Political Corner, 2026)
This study examines the resistance of the Pari Island community in fighting for the preservation of the Pari Island Nature Reserve, “Kepulauan Seribu” Regency, Jakarta Province. The coastal community is fighting against illegal reclamation and privatization that threaten their habitat and the natural preservation of the Pari Island Cluster. The study uses James C. Scott's resistance theory, which distinguishes between open resistance (public transcript) and hidden resistance (hidden transcript). Ethnographic research methods are used to understand the culture of community resistance in depth. The results show two forms of resistance with different characteristics. Open resistance is characterized by spontaneous and irregular, carried out individually for personal economic interests, and has a small impact, such as refusing basic food assistance from the company. Meanwhile, hidden resistance is more organized and effective. This form gave birth to the Pari Island Care Forum (Forum Peduli Pulau Pari/FPPP) in collaboration with WALHI Jakarta. This resistance is systematic and collective, using rational strategies for collective safety, including collecting evidence of environmental damage to sue the company. This movement is also emancipatory by spreading the narrative of the Right to Living Space through social media and murals to build public awareness of the Pari Island community when faced with incidental or repeated corporate practices.